Análise exploratória dos atendimentos do hospital Pequeno Príncipe - Tremel, Guilherme Graciano (2021)
Monograph made with the objective of developing a data exploratory analysis study, with emphasis on data visualization, using informations related to the Hospital Pequeno Principe care, located in Curitiba/PR. This analysis is based on a dataset generated by internal workers of the hospital and made available for educational usage, containing about 190 thousand records, from year 2012 to 2021. This monograph will approach the use of exploratory analysis deepening the utilization of Python programming, trying to obtain satisfactory results, evaluating whether they are relevant, in the possibility that they will be used for further study. This study addresses the perspective and possibility that in any area the study of data can provide promising results.